Metadata record for: A comprehensive, multisource database for hydrometeorological modeling of 14,425 North American watersheds - Scientific Data Curation Team (2020)
This dataset contains key characteristics about the data described in the Data Descriptor A comprehensive, multisource database for hydrometeorological modeling of 14,425 North American watersheds. Contents: 1. human readable metadata summary table in CSV format 2. machine readable metadata file in JSON format